Genetic prediction of micronutrient levels and the risk of colorectal polyps: a mendelian randomization study - Lv, Siyao; Ding, Yunyi; Huang, Junli; He, Yixin; Xie, Ruijie; Shi, Xiaohong; Ye, Wei (Clinical nutrition, 2024)
Objective - Previous epidemiological and experimental studies have yielded conflicting results regarding the influence of human micronutrient levels on the risk of colorectal polyps (CP). In our study, we conducted a two-sample Mendelian randomization (MR) investigation to probe the link between 13 human micronutrients (calcium, selenium, magnesium, phosphorus, folate, vitamins B-6, B-12, C, D, beta-carotene, iron, zinc, and copper) and the genetic susceptibility to CP. - Methods - Summary statistics for CP (n = 463,010) were obtained from pan-European genome-wide association studies, and instrumental variables for 13 micronutrients were screened from published genome-wide association studies (GWAS). After selecting suitable instrumental variables, we performed a two-sample MR study, deploying sensitivity analyses to judge heterogeneity and pleiotropy, using inverse variance weighted methods as our primary estimation tool. - Results - Our study identified that a genetic predisposition to elevated toenail and circulating selenium or serum β-carotene concentrations lowers the risk of CP occurrence. However, no statistically significant association was observed between the other 11 micronutrients and the risk of CP. - Conclusion - The study findings provide evidence that the micronutrient selenium and β-carotene may confer protective effects against the development of CP.